Analysing the Dual Impact of Gender and Job Qualifications on Career Progression in Indonesia’s Manufacturing Sector - Teguh Iman Santoso; Muhammad Nurwaskita Alamsyah (International Journal of Islamic Business and Management Review, 2024)
This study examines the influence of gender and job qualifications on career advancement, focusing on employees at PT Sanmina SCI Batam. Using a quantitative research design, data were collected from 248 respondents and analysed through multiple linear regression. The results indicate that both gender and job qualifications significantly impact career progression, with an R² value of 0.817, demonstrating the model's strong explanatory power. Gender disparities persist, disadvantaging women despite comparable qualifications to their male counterparts. The findings align with Social Role Theory and Human Capital Theory, emphasizing the interplay of societal norms and individual attributes in shaping career outcomes. Practical recommendations include mentorship programs, transparent promotion criteria, and leadership development initiatives to mitigate gender-based inequities. This research contributes to the literature by highlighting the complex interaction between gender and qualifications and advocating for equitable HR policies. Keywords Gender disparities, job qualifications, career advancement, Social Role Theory, Human Capital Theory